Cross Pollination’s Nomadic Laboratory: a praxis in-between practices - La Selva, Adriana Parente; Campbell, Patrick; Nie, Marije; Maciel, Andrea (Revista Brasileira de Estudos da Presença, 2021)
This collaborative writing presents the ways in which practitioner-researchers from Cross Pollination (CP), an international arts research platform with a focus on knowledge exchange, create nomadic and temporary laboratory spaces. It is argued that the encounter between different experiences of performative craft generates epistemic insights that enable members of the platform to rearticulate their practices through the reterritorialization of specialized techniques. Furthermore, the article discusses how an ethos of companionship may appear through dialogical and horizontal practices, contributing to a renewal of the theatre laboratory.